The relationship between the dietary inflammatory index and risk of total cardiovascular disease, ischemic heart disease and cerebrovascular disease: Findings from an Australian population-based prospective cohort study of women. (October 2016) - Vissers, Linda E.T.; Waller, Michael A.; van der Schouw, Yvonne T.; Hebert, James R.; Shivappa, Nitin; Schoenaker, Danielle A.J.M.; Mishra, Gita D.
Abstract: Background and aims: Recently, a pro-inflammatory diet based on a dietary inflammatory index (DII) has been related to higher CVD risk in general population, but this has not been investigated among women. Methods: We investigated the relationship between DII and risk of total CVD and CVD subgroups (myocardial infarction, ischemic heart disease, stroke and cerebrovascular disease) in a prospective cohort of 6972 Australian women aged 50–55 years at baseline in 2001. We used clinical and procedure information from inpatient hospital separation registries, information on use of health care services, and from the causes-of-death registry to ascertain CVD outcomes during 11-year follow up. The association between baseline DII score and cardiovascular endpoints was analysed through cox-regression, with correction for demographic and cardiovascular risk factors. Results: We identified 335 incident cases of CVD and 191 cases of ischaemic heart disease (including 69 myocardial infarctions) and 59 cases of cerebrovascular disease (including 40 cases of stroke). A statistically significant higher risk of myocardial infarction was observed in analyses using DII scores as a continuous variable with a hazard ratio of 1.46 (95% confidence interval 1.12–1.89), but this was attenuated by further adjustment for other known cardiovascular risk factors. No association was found for total CVD, ischaemic heart diseases, or cerebrovascular disease. Conclusions: There was no statistically significant association between the dietary inflammatory index and risk of total cardiovascular disease, ischemic heart disease, myocardial infarction, cerebrovascular disease or stroke in this population of mid-aged Australian women. Associations were not different for postmenopausal women. Highlights: The dietary inflammatory index (DII) was not associated with total CVD in mid-age women. No association was found between DII and myocardial infarction or stroke. Examining the relationships in postmenopausal women did not change the results.